Capacity for choice : Canada in a new North America - Hoberg, George (Policy research (Toronto, Ont.), 2002)
"Drawing together an interdisciplinary group of scholars, this collection of essays - part of the Trends Project of the Government of Canada's Policy Research Initiative - examines North American integration and its potential future impact on Canadian life. It looks at trends in integration, knowledge gaps, and policy implications in economics, culture, and politics." "The contributors argue that the consequences of continental integration have not been as formidable as many people believe - the reality turns out to be enormously complex and ambiguous. While Canada has surrendered some policy instruments in exchange for access to larger markets and the pressures for harmonization have probably increased, it still retains significant room to manoeuvre, even in areas of policy most affected by growing economic integration. Canada has formidable capacities for domestic policy choices in a wide range of sectors, as this volume clearly shows. It is up to Canadians and their elected officials to exercise that freedom, and the essays collected here can guide them in their choices, as they help to forge a new North America."--Jacket